Effects of edible mushroom addition and processing methods on the nutrient and functional properties of cocoyam flour - Blessing Edeh; Nkemjika Umerah; Josephat Ikechukwu Anyadioha (University of Sultan Ageng Tirtayasa, 2025)
Cocoyam is a rich source of carbohydrates but limited in protein and certain micronutrients. This study evaluated the effects of edible mushroom addition and various processing methods on the nutrient composition, and functional properties of cocoyam-based composite flour. Composite blends consisting of cocoyam and edible mushroom in a 70:30 ratio were prepared using different processing methods: raw (RACM), boiled (BOCM), roasted (ROCM), autoclaved (AUCM), and blanched (BLCM), with unprocessed 100% cocoyam flour (RACY) serving as the control. Standard analytical procedures were used for nutrient, antinutrient and functional properties assessment, and the results were statistically analyzed. The findings revealed notable improvements in the nutritional profile with mushroom inclusion. Protein content significantly increased from 2.59% in the control to 12.59% in the autoclaved sample (AUCM), while fiber content ranged from 4.45% to 6.90%, highest in BLCM. Ash content (3.82–4.97%) and fat content (0.25–1.83%) also improved. Carbohydrate content ranged from 66.13% to 75.30%, and energy value from 311.03 to 332.76 kcal/100g. Mineral content improved across samples, especially potassium (6.41–21.6 mg) and iron (2.19–8.44 μg). Functional properties such as bulk density (0.43–0.83 g/mL), water absorption (60.66–90.69 ml/g), and oil absorption (40.52–97.63 ml/g) showed significant variations, with blanched and autoclaved samples performing best. Anti-nutritional factors remained within acceptable safety limits. Overall, the addition of edible mushroom and application of appropriate thermal processing, particularly blanching and autoclaving, significantly enhanced the nutritional and functional properties of cocoyam flour, indicating its potential for use in developing nutrient-enriched functional foods.